2018
DOI: 10.1007/s10068-018-0495-x
|View full text |Cite
|
Sign up to set email alerts
|

Properties and bioavailability assessment of shrimp astaxanthin loaded liposomes

Abstract: This study aimed to investigate the effects of phospholipid composition on the properties and bioavailability of astaxanthin-loaded liposomes using cell culture. Two mixtures of phospholipids with different proportions of phosphatidylcholine (PC, 23% and 70%) were used at various concentrations (0.8, 1.6, and 2.0% w/v) to prepare astaxanthin-loaded liposomes, which were investigated for entrapment efficiency (EE), antioxidant activity, morphology and changes in astaxanthin properties during a storage period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 34 publications
(36 reference statements)
2
26
1
1
Order By: Relevance
“…[18] reported that liposome decreased the thermal oxidation of astaxanthin extracted from shrimp waste. In addition, [19] indicated that liposome made from phospholipid (phosphatidyl choline70%) at 2% (w/v) maintained the antioxidant activities of astaxanthin obtained from shrimp shell and the liposome showed a high a bioavailability by cellular uptake using cell culture.…”
Section: Introductionmentioning
confidence: 99%
“…[18] reported that liposome decreased the thermal oxidation of astaxanthin extracted from shrimp waste. In addition, [19] indicated that liposome made from phospholipid (phosphatidyl choline70%) at 2% (w/v) maintained the antioxidant activities of astaxanthin obtained from shrimp shell and the liposome showed a high a bioavailability by cellular uptake using cell culture.…”
Section: Introductionmentioning
confidence: 99%
“…In this research field, different lipid-based, organic, or inorganic-based and hybrid micro and nanoparticles, more or less complex, have been designed for improving the stability and bioavailability of astaxanthin [ 52 ]. Among them, the coacervates and the lipid-based micro/nanoparticles are the systems that have attracted the most attention in food industries [ 83 , 124 ], mainly due to the possibility to be scaled up.…”
Section: Effect Of the Encapsulation On The Bioactive Properties Omentioning
confidence: 99%
“…The free astaxanthin could then be solubilized into mixed micelles and be absorbed by passive diffusion or by specific epithelial transporters in the intestinal epithelium [ 83 ]. The composition and the physico-chemical and colloidal properties of the lipid-based particles will influence the bioaccessibility and bioavailability of astaxanthin, as well as the presence of specific components in foods, such as soluble dietary fiber, which compromise astaxanthin absorption [ 52 , 105 , 124 ]. Liposomes seem to be less resistant to degradation than nanostructured lipid carriers in the presence of bile acids and pancreatic lipases.…”
Section: Effect Of the Encapsulation On The Bioactive Properties Omentioning
confidence: 99%
“…Interfacial properties also have a strong influence on cellular uptake and absorption processes. In this sense, a recent study reported that the cellular uptake in Caco-2 cells of astaxanthin-loaded liposomes was improved when liposomes were formulated with 70% phosphatidylcholine [109]. On the other hand, another study described that cellular uptake of β-carotene in undifferentiated gastrointestinal epithelial cells (Caco-2 cells) depended on the emulsifier type added to the nanoemulsions rather than on the initial particle size of the nanoemulsions [110].…”
Section: Enhancing Absorption Of Lipophilic Bioactive Compounds In Epmentioning
confidence: 99%